Beyond beauty: A qualitative exploration of authenticity and its impacts on Chinese consumers' purchase intention in live commerce - Sun, Jiani; Dushime, Honorine; Zhu, Anding (Frontiers in Psychology, 2022)
Live commerce is a phenomenally innovative form of social commerce in China. In this paper, the authors aim to explore the authenticity of live commerce. By employing a qualitative approach using in-depth interviews and grounded theory, 21 initial categories are classified into six core categories. Among them, authenticity-associated concepts are classified into explicit concepts and implicit concepts. Explicit concepts of authenticity are associated with objectively authentic cues, while implicit concepts of authenticity are associated with subjectively authentic experiences. Moreover, the study explores the relationship between explicit concepts of authenticity and product commitment, as well as the relationship between implicit concepts of authenticity and affective commitment. Both of these paths are found to influence consumers' shopping-related behaviors. Although consumers can more easily perceive explicitly authentic cues than implicitly authentic experiences, this study suggests that the latter may be more effective in inducing shopping behaviors. In addition, the effect of streamer attractiveness on opinion leader building is addressed, while authenticity is found to be an alternative approach to attract consumers both for attractive and nonattractive streamers. Finally, the study addresses theoretical implications and practical implications as well as suggestions for future research.